Harmonization of sustainability standards under the WTO framework as the core to create an intersection of trade and environment mutually supportive - Papendieck, Sabine; Elverdin, Pablo (Instituto Interamericano de Cooperación para la Agricultura, 2021)
In the context of climate change the world faces growing environmental pressures described as planetary boundaries including air and water pollution, land degradation, natural resources depletion and extinctions of species among other environmental issues and, in particular, more frequently extreme weather-related events and natural disasters affecting negatively the human development.